Effect of finite temperature and external magnetic field on non-equilibrium transport in a single molecular transistor with quantum dissipation: Anderson-Holstein-Caldeira-Leggett model. (2022) - Bhattacharyya, Kuntal; Kalla, Manasa; Chatterjee, Ashok
Abstract: A magnetic field and temperature dependent quantum transport is investigated in a single molecular transistor. Our system is modelled by an onsite electron-electron correlation, polaronic interaction in the quantum dot and the coupling between quantum dot local phonon and the substrate phonon which produces a damping effect on the dynamics of the quantum dot. We use the Anderson-Holstein Hamiltonian along with the Caldeira-Leggett model to tackle the dissipation and polaronic effects and mean-field Hartree-Fock approximation to treat the onsite Coulomb correlation. We calculate transport properties such as spectral density function, tunnelling current, differential conductance employing finite-temperature Keldysh non-equilibrium Green function method under the influence of a finite temperature and an external magnetic field. It is shown that temperature has an intervening effect on the spin-resolved transport properties which can be used as a tuneable spin-filter.